Codesigning a Mental Health Discharge and Transitions of Care Intervention: A Modified Nominal Group Technique - Tyler, Natasha; Wright, Nicola; Grundy, Andrew; Gregoriou, Kyriakos; Campbell, Stephen; Waring, Justin (Frontiers in Psychiatry, 2020)
Background Discharge from acute mental health services has long been associated with mortality, risk and related adverse outcomes for patients. Many of the interventions that currently aim to reduce adverse outcomes, focus on a single group of healthcare professionals within a single healthcare setting. A recent systematic review highlights very few robust interventions that specifically aim to improve inter-operability across services. However the importance of promoting inter-agency working and improving information flow between services is continually highlighted as a key priority. Methods Using a novel co-design and experience based approach we worked with a multi-stakeholder group to develop possible solutions to reduce the adverse outcomes commonly associated with discharge from acute mental health services. This utilised a modified Nominal Group Technique and creative problem solving method to follow a four-stage process: Problem Identification, Solution Generation, Decision-Making, Prioritise and Implementation. Thirty-two healthcare professionals and an expert by lived experienced engaged with the process that took place over two stakeholder events. Results Stakeholders at the first event identified and agreed upon 24 potential ideas to improve discharge from acute mental health services. These were refined at the second event to four elements of an inter-agency intervention: a multi-agency ‘Discharge Team’ (with designated discharge coordinator), inclusive technology enabled team meetings, universal documentation and a patient generated discharge plan. Conclusion This is the first study to co-design an inter-agency mental health discharge intervention based around a discharge team. We developed a model for working that places a greater focus on a patient generated discharge plan, inter-agency working and information flow. A pilot of the proposed intervention is now needed to test feasibility and effectiveness in reducing adverse outcomes.